Synthesis and Characterization of Gambas (Luffa acutangula) Peel–Based Bioplastic Reinforced by Silica - Jasmine Rahma Kesuma Nirvana; Eni Budiyati; Akida Mulyaningtyas (Jurnal Kimia Sains dan Aplikasi, 2023)
Gambas (Luffa acutangula) plants contain a relatively high carbohydrate of 68.2%, whereas its peel contains 38.94% of carbohydrates and 20.6% of fibers. Gambas peels are rarely utilized and are typically discarded as food waste. Silica can be used as a filler and reinforcement material to improve the physical and mechanical properties. This study discussed synthesizing and characterizing bioplastics from Gambas peel reinforced by silica using polyvinyl alcohol (PVA) as a plasticizer with a mass of 8 g and 9 g and vinegar as a compatibilizer with volumes of 7 mL and 8 mL. The gelatinization temperature was adjusted at 85°C and 95°C. The synthesized bioplastics have improved mechanical characteristics due to the addition of PVA. The addition of vinegar as a compatibilizer revealed a homogenous mixture in surface morphological analysis. The highest performance of bioplastic samples was obtained from sample 7 with 8 mL vinegar, 9 g of PVA, and at 85°C of gelatinization temperature. The results showed that the maximum tensile strength reached 0.034 N/mm2, the elongation was 225%, the value of Young’s modulus was 0.015 N/mm2, the thermal stability reached 74.34% weight loss by heating up to 400°C, and the melting temperature reached at 220°C, the absorption of water was 37.61%, and the weight loss was 20.3% after ten days of soil burial.